2020
DOI: 10.1371/journal.pone.0233337
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of multiplicative and additive hyperbolic and hyperboloid discounting models in delayed lotteries involving gains and losses

Abstract: Many day-today decisions may involve risky outcomes that occur at some delay after a decision has been made. We refer to such scenarios as delayed lotteries. Despite human choice often involves delayed lotteries, past research has primarily focused on decisions with delayed or risky outcomes. Comparatively, less research has explored how delay and probability interact to influence decisions. Within research on delayed lotteries, rigorous comparisons of models that describe choice from the discounting framework… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(12 citation statements)
references
References 71 publications
(105 reference statements)
3
9
0
Order By: Relevance
“…Section Behavioral Models and Model Parameters), the obtained values are difficult to compare. However, the results are in line with the few studies who have considered the modified hyperboloid model and have shown its superiority [( 49 , 61 63 , 100 ); but see also ( 44 )], and which show that the hyperbolic model is not a comparably good fit ( 61 63 , 100 ).…”
Section: Discussionsupporting
confidence: 88%
See 4 more Smart Citations
“…Section Behavioral Models and Model Parameters), the obtained values are difficult to compare. However, the results are in line with the few studies who have considered the modified hyperboloid model and have shown its superiority [( 49 , 61 63 , 100 ); but see also ( 44 )], and which show that the hyperbolic model is not a comparably good fit ( 61 63 , 100 ).…”
Section: Discussionsupporting
confidence: 88%
“…Note though that this interpretation should be evaluated with caution since we observed a moderate correlation between s and κ in the reward condition. While a previous study evaluating the modified hyperboloid model did not find differences in the scaling parameter s between discounted rewards and losses (49), while others did not explicitly compare the parameters between tasks (38,61,62), the obtained results are in line with the frequent observation of lower discounting rates during loss discounting, also termed "sign-effect" [see also (41,111); for an overview see (112)]. This sign-effect was also reflected in the lower frequency of discounted choices for the loss condition as compared to the reward condition observed for all runs and experiments despite explicitly prolonging delays for this condition (see Supplementary Results S2.1-S2.3).…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations